The Effect of Small-Group Discussion through the ability to Write Procedure Texts by Seventh Grade Students of SMP Negeri 1 Atap Tampahan in Academic Year 2018/2019: The Effect of Small-Group Discussion through the ability to Write Procedure Texts by Seventh Grade Students of SMP Negeri 1 Atap Tampahan in Academic Year 2018/2019 - Mariati Saragih (Jurnal Mantik, 2020)
This study aims to determine whether there is an effect of the small-group discussion ability to write procedural text by VII grade students of SMP Negeri 1 Atap Tampahan in Academic Year 2018/2019. This study aims to: 1) describe the ability to write procedure text in content aspects; 2) to describe the ability to write procedure texts on structural aspects; 3) to describe the ability to write procedure texts on aspects of writing conventions; 4) to describe the ability to write procedure texts on aspects of linguistic characteristics. Research design is two group experimental research, which is applying the effect of the small group discussion ability to write procedure texts by students of SMP Negeri 1 Satu Atap Tampahan. The procedure of this research is the initial test (pre test) and the final test (post test) in the control class and the experimental class. The data of this study were analyzed descriptively. The results of the study showed that the seventh grade students of SMP Negeri 1 atap Tampahan obtained the average value of writing procedure texts in the control class that was 72.45 including the less category. In the aspect of content, the average value of students is less category (72.22). In the aspect of structure, the average value of students have good category (91.66). In the aspect of writing conventions, the average value of students is less category (50) and in the aspect of linguistic characteristics the average value of students is sufficient category (75.92). In the experimental class the average value obtained is 77.40 including the sufficient category. In the aspect of content, the average value of students is the sufficient category (80.76). In the aspect of structure, the average value of students is very capable (98.07). In the aspect of writing conventions, the average value of students is poor category (48.07). In the aspect of linguistic characteristics, the average value of students is sufficient category (82.69). In the classification of the ability to write the text of the control class procedure it is known that the sample that scores 75 and high score by 18 people (66.68%). While students who scored 75 and under numbered 9 people (33.32%). In the experimental class classification the ability to write procedure texts that score 75 and high score by 21 people (80.76%). While students who scored 75 and under numbered 5 people (19.24). From the results of the hypothesis test the t-test statistic is strengthened at a significant level of 5%, obtained tcount> ttable (0.05), which is 4.057> 1.67528, which can be concluded that there is a positive and significant effect of the small group discusssion on the ability to write procedure texts by VII grade students of State Junior High School 1 Atap Tampahan in Academic Year 2018/2019.